Enterprise Architecture Blueprint using the Zachman Framework: Mapping Processes, Data, and Technology for Digital Transformation - Andika Isma; Gusti Ayu Sri Adinda Prameswari; Nurul Fathiah Annisa D; Muh Fadel Mubarak; Salim Diarra (Indonesian Journal of Enterprise Architecture, 2025)
PT Elizabeth Hanjaya is a retail company operating in the fashion industry. Throughout its development, Elizabeth has been known for its unique characteristics, offering trendy, elegant, and high-quality fashion products at affordable prices. However, in terms of Information Systems/Information Technology (IS/IT) planning, the company has yet to fully maximize the utilization of Systems/Information Technology (IS/IT) that should be implemented within a company. Therefore, the company requires a more strategic planning to support its business objectives that align with the business and Systems/Information Technology (IS/IT) strategies. Enterprise Architecture Planning has been chosen as a guide, with the Zachman Framework as the method, consisting of six rows: scope, enterprise model, system model, technology constrained model, retailed representations, and functioning enterprise, as well as six columns: what, how, where, who, when, and why. The result of this research is a proposed architectural design that is expected to fully support the ongoing business operations to achieve optimal and effective outcomes.